Improvement of filtration performance of polyvinyl chloride/cellulose acetate blend membrane via acid hydrolysis. Issue 17 (2nd December 2020) - Zhang, Yong; Tan, Lin; Yao, Anrong; Tan, Pengfei; Guo, Ronghui; Zhou, Mi; Zhu, Puxin; Huang, Shijun; Wu, Yunheng
Abstract: Based on the hydrophilicity and biodegradability of cellulose acetate (CA), polyvinyl chloride (PVC)/CA blend membrane was prepared by solution comixing and phase transformation method. Then the CA in the blend membrane was partially hydrolyzed under acidic conditions to improve the hydrophilicity of the blend membrane, so as to improve the filtration performance of the PVC/CA blend membrane. The properties of the membranes were systematically characterized by Fourier transform infrared spectroscopy, differential scanning calorimeter, and scanning electron microscopy (SEM). The porosity, water contact angle, pure water flux (PWF), protein retention rate, and mechanical properties of the membrane were measured, and the effect of hydrolysis on the filtration performance of the blend membrane was analyzed. The results showed that the hydrophilicity and porosity of the blend membrane increased, the PWF and protein rejection rate enhanced after acid catalyzed hydrolysis, while the mechanical properties of PVC membrane were maintained. This simple preparation method endows PVC/CA blend membrane with desirable filtration performance, and also helps to overcome the disadvantages of poor hydrophilicity and easy pollution of pure PVC membrane. Abstract :